DEVELOPE THE CREATIVE THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS USING THE INQUIRY MODEL FOR NATURAL SCIENCES SUBJECT - Putri, Mufida Awalia (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
This study aims to provide an overview for educators and prospective educators in order to take advantage of research activities in the teaching of natural science, use the environment of school to give experimental habitual for students. This article describe the creative skills and guided inquiry model. the skills to think with the critical question is the problem and formulate appropriate hypotheses; take decisions and action steps such as designing the experiment; collect and assess information in accordance with the observations; and make conclusions. Inquiry model is a process that the teacher has to identify problems and provide much inducement to students in order to locate the problem and find alternative solutions through a scientific process and supported using creative and logical. After its use in the teaching of natural science, expected to educators and prospective educators can have an understanding that the research activities both lab and observation, the creative skills students grow, so they could face global competition in the 21st century.Â